The impact of text message reminders on cryotherapy uptake among women testing positive for HPV in western Kenya: a prospective cohort study - Yujung Choi; Saduma Ibrahim; Lawrence P. Park; Elizabeth A. Bukusi; Megan J. Huchko (BMC, 2024)
Abstract Background Mobile health (mHealth) has become an increasingly popular strategy to improve healthcare delivery and health outcomes. Communicating results and health education via text may facilitate program planning and promote better engagement in care for women undergoing human papillomavirus (HPV) screening. We sought to develop and evaluate an mHealth strategy with enhanced text messaging to improve follow-up throughout the cervical cancer screening cascade. Methods Women aged 25-65 participated in HPV testing in six community health campaigns (CHCs) in western Kenya as part of a single arm of a cluster-randomized trial. Women received their HPV results via text message, phone call, or home visit. Those who opted for text in the first four communities received "standard" texts. After completing the fourth CHC, we conducted two semi-structured focus group discussions with women to develop an "enhanced" text strategy, including modifying the content, number, and timing of texts, for the subsequent two communities. We compared the overall receipt of results and follow-up for treatment evaluation among women in standard and enhanced text groups. Results Among 2368 women who were screened in the first four communities, 566 (23.9%) received results via text, 1170 (49.4%) via phone call, and 632 (26.7%) via home visit. In the communities where enhanced text notification was offered, 264 of the 935 screened women (28.2%) opted for text, 474 (51.2%) opted for phone call, and 192 (20.5%) for home visit. Among 555 women (16.8%) who tested HPV-positive, 257 (46.3%) accessed treatment, with no difference in treatment uptake between the standard text group (48/90, 53.3%) and the enhanced text group (22/41, 53.7%). More women in the enhanced text group had prior cervical cancer screening (25.8% vs. 18.4%; p < 0.05) and reported living with HIV (32.6% vs. 20.2%; p < 0.001) than those in the standard text group. Conclusions Modifying the content and number of texts as an enhanced text messaging strategy was not sufficient to increase follow-up in an HPV-based cervical cancer screening program in western Kenya. A one-size approach to mHealth delivery does not meet the needs of all women in this region. More comprehensive programs are needed to improve linkage to care to further reduce structural and logistical barriers to cervical cancer treatment.